Complex sport analytics - Lebed, Felix (London ; New York : Routledge, 2017)
"This book is the first to combine principles from analytics, complex systems theory, multi-disciplinary diagnostics and sport performance analysis. It considers athletes, teams, and sport organisations in individual and team games as complex systems, and demonstrates how complexity studies can enrich analytics and give us a more sophisticated understanding of the causalities of winning and losing in sports. Part I introduces the basic categories of analytics and their uses in elite sport. Part II presents an original conception of sport analytics both as a complex of different kinds of processes and as a complexity adapted view of human systems acting in sport performance and management. Part III considers the main principles of complex sport analytics, expanding the prism of complexity to include all levels of a sport organisation from athletes, coaches and trainers to top decision makers, and suggests practical applications and simulations for cases of both individual and team sports. This is illuminating reading for any advanced student, researcher or practitioner working in sport analytics, performance analysis, coaching science or sport management" --
pt. 1. Preamble to sport analytics -- pt. 2. Basic principles of complex sport analytics -- pt. 3. LCR concept and its application in complex sport analytics.
Keywords: Sports -- Statistical methods; Performance -- Statistical methods; Sports -- Physiological aspects; Sports -- Psychological aspects